What Is This Thing Called Mentoring? - Darío Rodríguez (Sociologica)
Mentorship is an important academic formative activity with origins in medieval universities. It represents a form of collaborative self-learning that connects a professor with a student in the pursuit of knowledge. In the mentoring process, university life is replicated. The mentor needs the disciple to project their academic vocation beyond themselves. The student needs the mentor to academically channel their concerns and abilities. Although they need each other, their interest is selfless because their goal is knowledge, which transcends both of them.